Book Reviews - Das, Chandrima; Laskar, Samrat; Maszewski, Piotr; Sikorski, Grzegorz; Bhattacharjee, Anirban (Multicultural Shakespeare: Translation, Appropriation and Performance, 2015)
Miola, S. Robert, ed. Macbeth. By William Shakespeare. New York and London: W. W. Norton & Company, 2004. Pp. xxiii + 384. [South Asian Edition] Tiffany Ann Conroy Moore, Kozintsev’s Shakespeare Films: Russian Political Protest in Hamlet and King Lear. Jefferson, North Carolina, and London: McFarland & Company, 2012. Pp. viii + 194 Sosnowska, Monika. Hamlet uzmysłowiony (Sensuous Hamlet). Łódź: Wydawnictwo Uniwersytetu Łódzkiego, 2013. Pp. 201 Courtney, Krystyna Kujawińska and Monika Sosnowska, eds. Shakespeare 2014—w 450. rocznicę urodzin (Shakespeare 2014—For the 450th Anniversary of His Birth). Łódź: Wydawnictwo Uniwersytetu Łódzkiego, 2014. Pp. 235 Laura Estill, Dramatic Extracts in Seventeenth-Century English Manuscripts: Watching, Reading, Changing Plays. Delaware: University of Delaware Press, 2015. Pp. xxviii+255